2015
DOI: 10.1002/cbic.201402602
|View full text |Cite
|
Sign up to set email alerts
|

Triplex Crosslinking through Furan Oxidation Requires Perturbation of the Structured Triple‐Helix

Abstract: Short oligonucleotides can selectively recognize duplexes by binding in the major groove thereby forming triplexes. Based on the success of our recently developed strategy for furan-based crosslinking in DNA duplexes, we here investigated for the first time the use of the furan-oxidation crosslink methodology for the covalent locking of triplex structures by an interstrand crosslink. It was shown that in a triplex context, although crosslinking yields are surprisingly low (to nonexistent) when targeting fully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…In contrast to the earlier developed DNA based probes, 33 we expected the here developed PNA-furan probes to offer the possibility to target double stranded DNA. We thus tested their ability to form ICLs in a strand displacement test.…”
mentioning
confidence: 89%
“…In contrast to the earlier developed DNA based probes, 33 we expected the here developed PNA-furan probes to offer the possibility to target double stranded DNA. We thus tested their ability to form ICLs in a strand displacement test.…”
mentioning
confidence: 89%
“…Our group therefore started exploring the use of furan moieties as masked aldehydes for a novel cross-linking technology. [55][56][57][58][59][60][61][62][63][64][65][66][67] Owing to the stability of the furan moiety before oxidation, a large series of furan derivatives is readily available. Moreover, the moiety is compatible with most of the standard chemistries used for modified nucleoside, amino acid, ODN and peptide synthesis.…”
Section: A Maddermentioning
confidence: 99%
“…The results are also in line with another related work that studied the crosslinking reaction of furan-modified DNAs at the internal position and the 3'-end of the DNA strand with a duplex DNA via the triplex formation. [22] In this case, the furan was incorporated as a base surrogate, and it was observed that the crosslinking with the internally furan-modified probe could take place only with the single-stranded DNA target but not with the duplex DNA target due to the unavailability of the nucleobase. On the other hand, the crosslink readily formed in the case of 3'-furan modified probe with both single-stranded and duplex DNA targets.…”
Section: Discussionmentioning
confidence: 99%
“…[21] Furthermore, crosslinkable ODN probes were applied to target double-stranded DNA by triplex formation. [22] A similar strategy has been applied to target proteins by crosslinking with a furan-modified peptide ligand. [23] Interestingly, the crosslinking spontaneously occurred in several cell lines, presumably via the oxidation by endogenously produced reactive oxygen species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation